Getting a MUVE On : Developing Web 2.0 Curricula in the Australian Humanities Final Report. - Matthews, Carol; Agutter, Karen (Office for Learning and Teaching, 2014)
The past decade has seen an explosion in the use of multi-user virtual environments (MUVEs) in education. This has predominantly occurred in the United States and the United Kingdom, in the sciences and health sciences. This is the final report from a project that broke new ground in several ways. Firstly, it evaluates Web 2.0 technologies in the humanities in which they have yet to be studied critically to any significant depth. Using a reconstruction of eighteenth-century London in Second Life, students were able to explore and experience the world in which the texts and events they study were created in a way books, articles and even DVDs cannot match. Secondly, the project approached MUVEs from an Australian perspective: observing and recording the pedagogical and practical benefits and challenges of learning and teaching within a virtual environment. In other words, the project conducted a critical study of Web 2.0 technology to develop humanities curriculums which meet the present and future needs of both students and universities.